A mean of dependent normal variables maximum - Agnė Burauskaitė; Algimantas Aksomaitis (Lietuvos Matematikos Rinkinys)
A mean value of normal sequence maximum is analyzed. In a case of standard normal variables, for n ≤ 5 (n – a length of sequence), there are formulas to express every order moments of extremes using elementary functions. For longer sequences it is not possible. Also there are analogous formulas for a mean value of two and three dependent normal variables [1]. In this work we study a relation between mean values of dependent and independent variables maxima. It is shown that there is a possibility to calculate a mean value of dependent normal variables maximum using the result of independent case. To test the relation we use computer simulation.